2017
DOI: 10.1111/1750-3841.13702
|View full text |Cite
|
Sign up to set email alerts
|

Processes to Preserve Spice and Herb Quality and Sensory Integrity During Pathogen Inactivation

Abstract: Selected processing methods, demonstrated to be effective at reducing Salmonella, were assessed to determine if spice and herb quality was affected. Black peppercorn, cumin seed, oregano, and onion powder were irradiated to a target dose of 8 kGy. Two additional processes were examined for whole black peppercorns and cumin seeds: ethylene oxide (EtO) fumigation and vacuum assisted‐steam (82.22 °C, 7.5 psia). Treated and untreated spices/herbs were compared (visual, odor) using sensory similarity testing protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The quality attributes such as color and aroma are important for spice products, and these quality attributes could potentially be affected by a significant increase in temperature during processing such as disinfection or grinding (Duncan et al., 2017; Ghodki & Goswami, 2016). Ghodki and Goswami (2016) showed that the grinding temperature at 40 °C affected color and volatile oil of black pepper powder compared to grinding at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality attributes such as color and aroma are important for spice products, and these quality attributes could potentially be affected by a significant increase in temperature during processing such as disinfection or grinding (Duncan et al., 2017; Ghodki & Goswami, 2016). Ghodki and Goswami (2016) showed that the grinding temperature at 40 °C affected color and volatile oil of black pepper powder compared to grinding at a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Retaining color characteristics in spices is crucial to prevent the discoloration of the final food product (Duncan et al., 2017). Table 1 shows the color of black peppercorns before and after PUV treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial reduction has often been described as loglinear in the past, but the current study indicated a more complex trend of reduction during steam treatments, as can be seen in the high RMSE and low R 2 adj ( Table 1). In a parallel study from our group, the effects of vacuum steam pasteurization for a 2 min dwell time on the quality of peppercorns and cumin seeds was analyzed (Duncan et al, 2017). No differences in visual appearance for whole black peppercorns were noted based on sensory similarity testing.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation is a decontamination method that can be applied effectively to all spices such as black and white pepper, cinnamon, nutmeg, cumin seeds, and aromatic herbs such as parsley and basil oregano sage onion powder (Calucci et al., 2003; Duncan et al., 2017; Emam, Farag, & Aziz, 1995; Sádecká, 2007). This technique causes little sensory modification because few volatile compounds are eliminated.…”
Section: Decontamination Methods For Spices and Herbsmentioning
confidence: 99%